ترجيحات بن رشد للاحكام الفقهية بالمقاصد من خلال كتابة بداية المجتهد -باب البيوع أنموذجا- - رمضاني, نعيمة (University of Eloued-جامعة الوادي, 2014)
In a number of cases, Provisions drawn from evidence in the Shari’ah (Islamic law) seemed to be contradictory. Therefore, the scholars alleviated this contradiction by different means,of which “weighting”-i.e. givingadvantage to one of the conflicting evidence - was the most important. Some scholars tried to put an end to this contradiction by weighting the purposes (maquasid) of Shari’ah. IbnRushd was one of the most prominent in the Maliki school. In his book “KhulasatBidayat al Mudj’tahid”- (Averröes’s Premier of the Jurist: Synopsis and Commentary), he relied on weighting the purposes of Shari’ah to mitigate the conflicting opinions of the scholars. Through induction and research, I consider Imam IbnRushd an objective jurist who relies on accuracy and analysis in weighting the purposes of Shari’ah. In his book, he sometimes chooses the opinion of the majority of the scholars over his own school’s. The issue of the choice of the council which he tackled unlike the Malikis after considering the purpose of its permission or prohibition is an example. I mentioned from his book several issues relating to sales where he relied on weighting the purposes of Shari’ahto set their rules.
مذكرة ماستر
Keywords: ترجيحات- بن رشد - المقاصد-بداية المجتهد-; Weightings - Ibn Rushd - the purposes - the beginning of the diligent -